A method for preparing a negative electrode of a metal oxide lithium-ion battery with a hierarchical pore structure

The negative electrode of the graded pore structure metal oxide lithium-ion battery was prepared by combining hydrothermal method and interdiffusion-sintering method, which solved the performance attenuation problem caused by volume expansion of the lithium-ion battery negative electrode material during charging and discharging, achieved efficient cycling performance and rate performance, and reduced production costs.

CN115425183BActive Publication Date: 2025-03-25SICHUAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211230806.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-08
Publication Date
2025-03-25
Estimated Expiration
2042-10-08

AI Technical Summary

Technical Problem

The volume expansion of the negative electrode materials of existing lithium-ion batteries during charging and discharging leads to powdering, shedding of the active material and damage to the electrode conductive network, thereby rapidly attenuating capacity and cycling performance. At the same time, the preparation process is complex and costly, making it difficult to achieve large-scale industrial production.

Method used

The negative electrode of the graded pore structure metal oxide lithium ion battery was prepared by a combination of hydrothermal method and interdiffusion-sintering method. Through this method, a composite structure of large pores at the sub-micron to micron scale and small pores at the nanoscale was generated, thereby improving the specific surface area of ​​the negative electrode and the efficiency of electrode reaction.

Benefits of technology

It significantly improves the circulation performance and rate performance of the negative electrode of lithium-ion battery, reduces production costs, avoids the powdering and shedding of active materials, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115425183B_ABST
    Figure CN115425183B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a negative electrode of a metal oxide lithium ion battery with a hierarchical pore structure, wherein a mixed solution A of a metal chloride and N,N-dimethylformamide and a mixed solution B of sodium hydroxide and selenium oxide are placed in a reactor and mixed evenly, and after fully reacting at a suitable temperature in a blast drying oven, metal selenide nanoparticles are obtained by washing and drying; the metal selenide nanoparticles are then pressed into sheets using a tablet press, and placed in a tube furnace for high-temperature sintering, and the metal selenide reacts with oxygen to generate metal oxides and selenium oxide, and the high-temperature sublimation of selenium oxide leaves nanometer-scale pores in the original position, and the sintering of the metal selenide causes the formation of submicron to micrometer-scale macropores between the particles, i.e., a negative electrode of a metal oxide lithium ion battery with a hierarchical pore structure is obtained. The preparation method provided by the present invention can simplify the production process of the negative electrode of a lithium ion battery and effectively improve the cycle performance and rate performance of the negative electrode of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery negative electrodes and relates to a method for preparing a graded pore structure metal oxide lithium ion battery negative electrode. Background Art

[0002] At present, global oil and other fossil energy sources are becoming increasingly scarce, leading to more urgent needs for countries around the world to develop renewable energy sources such as wind power, solar energy, and tidal energy. However, the intermittent and volatile supply of such renewable energy sources makes it difficult to be widely used. The introduction of advanced energy storage and conversion technologies can continuously and stably supply such volatile energy to the audience through storage and conversion. Therefore, in order to effectively improve the stability of new energy systems and expand their future application scope, it is necessary to develop efficient and clean energy storage and conversion devices so that new energy technologies can effectively solve the energy problems facing mankind.

[0003] Among the various existing energy storage devices and systems, lithium-ion batteries have been widely used in various electronic devices due to their advantages such as high output voltage, high energy conversion efficiency, long cycle life and no memory effect. In particular, they have shown broad application potential in electric vehicle power systems, making lithium-ion batteries one of the current research hotspots in the fields of materials science and energy science.

[0004] The negative electrode material is the key to determining the capacity and life of lithium-ion batteries. The currently widely used commercial negative electrode material is graphite-based material, which has the advantages of low discharge platform and stable cycle performance. However, since its application, its actual specific capacity has been close to the theoretical level (372 mAh / g), which will be difficult to meet the development needs of high-energy-density power batteries in the future. Therefore, the development of new high-specific-capacity negative electrode materials is an important development direction in the field of lithium-ion batteries.

[0005] Metal oxides (M x O y , M=Fe, Cu, Sn, Ni, etc.) has a high theoretical specific capacity, is inexpensive, environmentally friendly, and easy to prepare, and is considered to be the most promising negative electrode material for the next generation of lithium-ion batteries. However, it will produce a huge volume expansion effect during the charge and discharge process, which can easily lead to the pulverization and shedding of active materials and the destruction of the electrode conductive network, thereby causing the capacity and cycle performance of lithium-ion batteries to decay rapidly.

[0006] L. Noerochim et al. (Sun M, Sun M, Yang H, et al. Porous Fe 2 O 3nanotubes as advanced anode for high performance lithium ion batteries[J]. CeramicsInternational, 2017, 43(1): 363-367.) discloses a high-capacity Fe 2 O 3 Preparation method of negative electrode material. 3 •6H 2 O as a precursor, prepare 1 mol / L FeCl 3 30 mL of the solution was mixed with 2 mol / L lysine and stirred with a magnetic stirrer for 30 min. The solution was then transferred to a 120 mL reactor and kept at 180 °C in a muffle furnace for 12 h. The precipitate produced in the solution was then separated by a centrifuge for 45 min to obtain the sediment, which was washed several times with deionized water and baked in an oven at 90 °C for 24 h to obtain Fe 2 O 3 Negative electrode active material powder. 2 O 3 The negative electrode active material powder was mixed with carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 80:15:5, and N-methylpyrrolidone was added to obtain a paste. The paste was then evenly coated on a 1 cm 2 The copper foil was baked in an oven at 100 °C for 12 h and then assembled into a coin cell as a working electrode.

[0007] This method has the following shortcomings that need to be improved: (1) The preparation process used is relatively complex, costly, and difficult to achieve industrial large-scale production; (2) The method of coating the negative electrode active material powder has a weak bonding force between the active material and the current collector, and the conductivity is poor, resulting in poor rate performance and rapid capacity decay. Summary of the invention

[0008] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a negative electrode of a lithium ion battery with a hierarchical pore structure metal oxide by combining a hydrothermal method with an interdiffusion-sintering method, so as to improve the cycle performance and rate performance of the negative electrode of the lithium ion battery and reduce the production cost of the negative electrode material of the lithium ion battery.

[0009] The present invention provides a method for preparing a negative electrode of a metal oxide lithium-ion battery with a hierarchical pore structure, and the steps are as follows: (1) firstly prepare N,N-dimethylformamide (DMF) and metal chloride (MCl a ) mixed solution A and sodium hydroxide (NaOH) and selenium oxide (SeO 2) Mix solution B. Place appropriate amounts of solution A and solution B in the reactor and mix them evenly using an ultrasonic machine. Then place the reactor in a blast drying oven, set the temperature to 100~300 ℃, and keep it warm for 12~72 hours. In the specific high temperature and high pressure environment in the reactor, MCl a and SeO 2 The reaction is complete to obtain metal selenide (M x Se y ) nanoparticle precursor powder; (2) the M prepared in step (1) x Se y The nanoparticle precursor powder is filtered with a suction filter, and the obtained nanoparticles are washed. After washing, the powder is placed in a vacuum drying oven for drying, and the dried powder is pressed into a whole sheet using a tablet press. x Se y The sheet is placed in a tube furnace and the temperature is set between 500 and 1300 °C for high temperature sintering. x Se y Reacts with oxygen in the air to generate M x O y with SeO 2 .SeO 2 The sublimation temperature of SeO is lower than 400 °C, so at the above-mentioned heat treatment temperature, 2 Gasification, its original position in the sheet will form nano-scale holes, and M x Se y During the sintering process of the nanoparticles, due to the different sintering degrees between the particles, large pores of submicron to micron scale are formed between the particles, thus obtaining an integrated negative electrode of a metal oxide lithium-ion battery with a hierarchical pore structure.

[0010] In the preparation method of the above-mentioned graded pore structure metal oxide lithium ion battery negative electrode, the applicable scope of the graded pore structure metal oxide lithium ion battery negative electrode includes iron oxides, namely ferric oxide, ferric oxide, ferrous oxide, a mixture of ferric oxide and ferrous oxide, a mixture of ferric oxide and ferrous oxide, a mixture of ferric oxide and ferrous oxide, and a mixture of ferric oxide, ferric oxide and ferrous oxide; copper oxides, namely cupric oxide, cuprous oxide, and a mixture of cupric oxide and cuprous oxide; tin oxides, namely tin dioxide, stannous oxide, and a mixture of tin dioxide and stannous oxide; nickel oxides, namely nickel oxide, nickel nitride, and a mixture of nickel oxide and nickel nitride.

[0011] In the above method for preparing a negative electrode for a metal oxide lithium-ion battery with a hierarchical pore structure, the thickness of the negative electrode for a metal oxide lithium-ion battery with a hierarchical pore structure is preferably 200-600 μm.

[0012] In the above-mentioned method for preparing the negative electrode of the hierarchical pore structure metal oxide lithium ion battery, the MCl in solution A a The concentration is preferably 0.5~3 mol / L, DMF and MCl a The volume ratio of SeO in solution B is preferably 15:1~25:1; 2 The concentration is preferably 0.5-3 mol / L, the NaOH concentration is preferably 0.5-4 mol / L; the volume ratio of solution A to solution B is preferably 5:1-12:1.

[0013] In the above-mentioned method for preparing a negative electrode for a metal oxide lithium-ion battery with a hierarchical pore structure, the insulation temperature of the reactor in the blast drying oven in step (1) is preferably 100-220° C., and the insulation time is preferably 24-72 h.

[0014] In the above-mentioned method for preparing the negative electrode of the metal oxide lithium-ion battery with a hierarchical pore structure, the drying temperature of the vacuum drying oven is preferably 50-100°C, and the insulation time is preferably 6-24 h.

[0015] In the above-mentioned method for preparing the negative electrode of the hierarchical pore structure metal oxide lithium ion battery, in step (1), M is prepared by a hydrothermal method. x Se y When the nanoparticle precursor powder is used, the chemical reaction that occurs is as follows: MCl a +SeO 2 →M x Se y +O 2 +Cl 2 (1).

[0016] In the above-mentioned method for preparing the negative electrode of the metal oxide lithium ion battery with hierarchical pore structure, in step (2), M x Se y The nanoparticle precursor powder is preferably cleaned by alternating deionized water and anhydrous ethanol for 4 to 5 times.

[0017] In the above-mentioned method for preparing the negative electrode of the metal oxide with a hierarchical pore structure for a lithium-ion battery, the pressure at which the tablet press presses the powder into tablets is preferably 30-80 MPa.

[0018] In the above-mentioned method for preparing the negative electrode of the hierarchical pore structure metal oxide lithium ion battery, in step (2), M x Se y The heating rate of the sheet sintered in a tubular furnace is preferably 10-15 °C / min, the heat treatment temperature is preferably 700-900 °C, and the heat treatment time is preferably 2-4 h.

[0019] In the above-mentioned method for preparing the negative electrode of the metal oxide lithium ion battery with a hierarchical pore structure, when the integrated negative electrode of the metal oxide lithium ion battery with a hierarchical pore structure is prepared by the interdiffusion-sintering method in step (2), the chemical reaction that occurs is as follows: x Se y +O 2 →M x O y +SeO 2 (2).

[0020] In the above-mentioned method for preparing the negative electrode of the hierarchical pore structure metal oxide lithium ion battery, during the sintering process, M x Se y Reacts with oxygen in the air to generate M x O y with SeO 2 .SeO 2 The sublimation temperature of SeO is lower than 400 °C, so at the above-mentioned heat treatment temperature, 2 Gasification, its original position in the sheet will form nano-scale holes, and M x Se y During the sintering process of nanoparticles, due to the different sintering degrees between particles, macropores ranging from submicron to micron are formed between the particles, where the pore size of the macropore is 0.4~25 μm and the pore size of the micropore is 20~90 nm.

[0021] The hierarchical pore structure metal oxide lithium ion battery integrated negative electrode provided by the present invention has a morphological feature of a composite of a submicron to micron scale macroporous structure and a nanometer scale small pore structure. The submicron to micron pores are evenly distributed throughout the negative electrode, and the nanopores are evenly distributed in the solid area separated by the submicron to micron pores. The uniform distribution of submicron to micron pores and nanopores increases the specific surface area of ​​the negative electrode, can increase the contact area between the electrolyte and the negative electrode, and provide more attachment sites for lithium ions, thereby promoting the electrode reaction; in addition, the hierarchical pore structure can also provide a transmission channel for ions and charges, shorten the reaction time, reduce polarization, and inhibit the increase of the internal resistance of the lithium ion battery; the abundant pores can buffer the volume expansion effect of the negative electrode during the charging and discharging process, reduce the destructive effect on the negative electrode, and is conducive to enhancing the cycle performance of the electrode; the synthesis of the integrated negative electrode can avoid the contamination of active materials and the use of auxiliary additives such as binders, and effectively reduce the occurrence of active particle pulverization and shedding. Under the combined effect of the above factors, the present invention plays a role in improving the electrochemical properties of the negative electrode material of the lithium ion battery.

[0022] Compared with the prior art, the technical solution provided by the present invention produces the following technical effects.

[0023] 1. The present invention provides a method for preparing a negative electrode of a metal oxide lithium ion battery with a hierarchical pore structure. It only needs to prepare a precursor powder by hydrothermal synthesis, and then prepare an integrated negative electrode of a metal oxide lithium ion battery with a hierarchical pore structure by an interdiffusion-sintering method. The electrode prepared by this method does not need to add auxiliary additives such as a binder, which can avoid electrode contamination, hinder electron transmission, increase electrode polarization and impedance, and the preparation method is simple and the conditions are mild, which improves the traditional process for preparing porous oxide electrodes and improves electrode performance. Compared with the prior art, the preparation method described in the present invention is simpler, which is conducive to reducing the production cost of lithium ion battery negative electrodes and making it easier to achieve large-scale production of lithium ion negative electrodes.

[0024] 2. The main component of the negative electrode of a lithium-ion battery with a hierarchical pore structure described in the present invention is a metal oxide, which shows the characteristics of uniform distribution of submicron to micron-scale macropores and nanoscale pores inside the sample at a microscopic level. The submicron to micron-scale macropores are uniformly distributed throughout the negative electrode, and the nanoscale pores are uniformly distributed in the solid area separated by the submicron to micron pores. The hierarchical pore structure existing in the electrode can well buffer the volume changes occurring during the charge and discharge process; at the same time, the uniform distribution of the hierarchical pores increases the specific surface area of ​​the negative electrode, can increase the contact area between the electrolyte and the negative electrode, and provide more attachment sites for lithium ions, thereby promoting the electrode reaction; the synthesis of the integrated negative electrode can avoid the contamination of active materials and the use of auxiliary additives such as binders, effectively reduce the occurrence of pulverization and shedding of active particles, and significantly improve the problems of poor electrode cycle stability and low first coulomb efficiency.

[0025] 3. The iron oxide lithium ion battery negative electrode prepared by the method of the present invention is assembled into a lithium ion battery, and the charge and discharge current density is 1 mA / cm 2 After 290 cycles, the specific capacity can still be maintained at a stable level, with a charge area specific capacity of 1.05 mAh / cm 2 The capacity attenuation rate is about 50%. At the same time, the Coulomb efficiency remains above 98% after 10 cycles, and the Coulomb efficiency remains stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is FeSe in Example 1 2 SEM images of nanoparticle precursor powders.

[0027] Figure 2 It is FeSe in Example 1 2 XRD patterns of nanoparticle precursor powders.

[0028] Figure 3 It is FeSe in Example 1 2EDS spectrum of nanoparticle precursor powder.

[0029] Figure 4 This is a low-magnification SEM photograph of the negative electrode of the hierarchical pore structure iron oxide lithium-ion battery in Example 1.

[0030] Figure 5 This is a high-magnification SEM photograph of the negative electrode of the iron oxide lithium-ion battery with a hierarchical pore structure in Example 1.

[0031] Figure 6 This is the XRD spectrum of the negative electrode of the hierarchical pore structure iron oxide lithium ion battery in Example 1.

[0032] Figure 7 This is the EDS spectrum of the negative electrode of the hierarchical pore structure iron oxide lithium ion battery in Example 1.

[0033] Figure 8 It is the constant current charge and discharge cycle performance curve of the lithium ion battery prepared in Example 1.

[0034] Fig. 9 This is a low-magnification SEM photograph of the hierarchical pore structure iron oxide lithium-ion battery negative electrode prepared in Example 2.

[0035] Fig.10 This is a high-magnification SEM photograph of the hierarchical pore structure iron oxide lithium-ion battery negative electrode prepared in Example 2.

[0036] Fig.11 This is the XRD spectrum of the hierarchical pore structure iron oxide lithium ion battery negative electrode prepared in Example 2.

[0037] Fig.12 This is the constant current charge and discharge cycle performance curve of the lithium ion battery prepared in Example 2. DETAILED DESCRIPTION

[0038] The following examples further illustrate the preparation method of the negative electrode of the metal oxide lithium ion battery with a hierarchical pore structure provided by the present invention. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The technical personnel in the relevant field make some non-essential improvements and adjustments to the present invention according to the above invention content for specific implementation, which still falls within the scope of protection of the present invention.

[0039] Example 1

[0040] In this embodiment, a method for preparing a negative electrode of an iron oxide lithium-ion battery with a hierarchical pore structure is provided, and the specific steps are as follows.

[0041] (1) Add 1 mL 1.5 mol / L FeCl 3The solution was mixed evenly with 20 mL of N,N-dimethylformamide to form solution A. 1 mL of 2 mol / L NaOH solution was added to 1 mL of 2 mol / L SeO 2 The solution was mixed evenly to obtain solution B. Then, solution A and solution B were poured into a 50 mL reactor, and the reactor was placed in a forced air drying oven, and the insulation temperature was set to 200 °C for 48 h.

[0042] (2) FeSe prepared in step (1) 2 The nanoparticle precursor powder was filtered with a suction filter and washed with deionized water and anhydrous ethanol for 4 times. After washing, it was placed in a vacuum drying oven for drying at 65 °C for 12 h. The dried powder was pressed into tablets with a tablet press at a pressure of 50 MPa. 2 The sheet was placed in a tube furnace, the heat treatment temperature was set to 700 °C, and the temperature was raised to 700 °C at a heating rate of 10 °C / min in an air atmosphere and kept at this temperature for 2 h for high temperature sintering. 2 Reacts with oxygen in the air to generate Fe 2 O 3 with SeO 2 , SeO 2 The sublimation temperature of SeO is lower than 400 °C. Under the condition of heat treatment at 700 °C, 2 Gasification will form nanoscale holes in the original position of the sheet; while FeSe 2 During the sintering process of the nanoparticles, due to the different sintering degrees between the particles, large pores of micrometer scale are formed between the particles, thus obtaining an integrated negative electrode of iron oxide lithium-ion battery with a hierarchical pore structure.

[0043] Figures 1 to 3 They are respectively the FeSe after cleaning and drying in step (2) 2 SEM photos, XRD spectra and EDS spectra of nanoparticle precursor powder. Figures 1 to 3 It can be seen that in step (1), the hydrothermal method prepared particles with a diameter range of 200-3000 nm. XRD analysis showed that the particle composition phase is FeSe 2 . Figure 4 and Figure 5 They are SEM photos of the hierarchical pore structure iron oxide lithium ion battery negative electrode prepared in step (2) at different magnifications. Figure 6 and Figure 7 The XRD and EDS spectra of the prepared hierarchical pore structure iron oxide lithium ion battery negative electrode are respectively. Figures 4 to 7 It can be seen that the FeSe in step (2)2 After the nanoparticle precursor powder is sintered in an oxygen atmosphere, the product is Fe 2 O 3 Its morphological characteristics at the microscopic level are a combination of a micron-scale macropore structure and a nano-scale micropore structure. The micropores are evenly distributed throughout the negative electrode, while the nanopores are evenly distributed in the solid area separated by the micropores. From the SEM image, it can be seen that the pore size distribution of the macropores is approximately 3~9 μm, and the pore size distribution of the micropores is approximately 50~90 nm.

[0044] The lithium ion battery negative electrode prepared in this example is used to make a lithium ion battery and perform a performance test.

[0045] The metal lithium sheet was used as the counter electrode, the negative electrode prepared in this example was used as the working electrode, microporous polypropylene was used as the separator, and 1M lithium hexafluorophosphate (LiPF 6 ) was used as the electrolyte, in which the volume ratio of EC, DMC and DEC was 1: 1: 1. The lithium-ion battery was assembled in a glove box filled with argon gas and the water and oxygen content were both less than 1 ppm. The obtained lithium-ion battery was tested using a constant current charge and discharge instrument modeled NEWARE BTS~610. The current density during the test was 1 mA / cm 2 , voltage range is 0.01~ 3.0 V (vs. Li / Li + ), the test temperature is room temperature.

[0046] Test results such as Figure 8 As shown in the figure, it can be seen that when the charge and discharge current density of this example is 1 mA / cm 2 After 290 cycles, the specific capacity can still be maintained at a stable level, with a charge area specific capacity of 1.05 mAh / cm 2 The capacity attenuation rate is about 50%. At the same time, the Coulomb efficiency remains above 98% after 10 cycles, and the Coulomb efficiency remains stable.

[0047] Example 2

[0048] In this embodiment, a method for preparing a negative electrode of an iron oxide lithium-ion battery with a hierarchical pore structure is provided, and the specific steps are as follows.

[0049] (1) Add 2 mL of 1 mol / L FeCl 3 The solution was mixed evenly with 20 mL of N,N-dimethylformamide to form solution A. 2 mL of 4 mol / L NaOH solution was added to 2 mL of 2 mol / L SeO 2The solution was mixed evenly to obtain solution B. Then, solution A and solution B were poured into a 50 mL reactor, and the reactor was placed in a forced air drying oven, the temperature was set to 180 °C, and the temperature was kept for 60 h.

[0050] (2) FeSe prepared in step (1) 2 The nanoparticle precursor powder was filtered with a suction filter and washed with deionized water and anhydrous ethanol for 5 times. After washing, it was placed in a vacuum drying oven for drying at 65 °C for 24 h. The dried powder was pressed into tablets with a tablet press at a pressure of 60 MPa. 2 The sheet was placed in a tube furnace, the heat treatment temperature was set to 900 °C, and the temperature was raised to 900 °C at a heating rate of 13 °C / min in an air atmosphere and kept at this temperature for 2 h for high temperature sintering. 2 Reacts with oxygen in the air to generate Fe 2 O 3 with SeO 2 , SeO 2 The sublimation temperature of SeO is lower than 400 °C. Under the condition of heat treatment at 900 °C, 2 Gasification will form nanoscale holes in the original position of the sheet; while FeSe 2 During the sintering process of the nanoparticles, due to the different sintering degrees between the particles, large pores of submicron to micron scale are formed between the particles, thus obtaining an integrated negative electrode of an iron oxide lithium-ion battery with a hierarchical pore structure.

[0051] Figures 9-11 They are respectively the low-magnification SEM photo, high-magnification SEM photo and XRD spectrum of the hierarchical pore structure iron oxide lithium-ion battery negative electrode prepared in step (3). Figures 9-11 It can be seen that the FeSe in step (2) 2 After the nanoparticle precursor powder is sintered in an oxygen atmosphere, the product is Fe 2 O 3 Its microscopic morphology is a composite of submicron to micron-scale macropores and nanometer-scale micropores. The submicron to micron pores are evenly distributed throughout the negative electrode, while the nanopores are evenly distributed in the solid area separated by the submicron to micron pores. From the SEM images, it can be seen that the pore size distribution of the macropores is roughly 0.4~6 μm, and the pore size distribution of the small pores is roughly 30~80 nm.

[0052] The lithium ion battery negative electrode prepared in this example is used to make a lithium ion battery and perform a performance test.

[0053] The metal lithium sheet was used as the counter electrode, the negative electrode prepared in this example was used as the working electrode, microporous polypropylene was used as the separator, and 1M lithium hexafluorophosphate (LiPF 6 ) was used as the electrolyte, in which the volume ratio of EC, DMC and DEC was 1: 1: 1. The lithium-ion battery was assembled in a glove box filled with argon gas and the water and oxygen content were both less than 1 ppm. The obtained lithium-ion battery was tested using a constant current charge and discharge instrument modeled NEWARE BTS~610, with a current density of 3 mA / cm 2 , voltage range is 0.01~ 3.0 V (vs. Li / Li + ), the test temperature is room temperature.

[0054] Test results such as Fig.12 As shown in the figure, it can be seen that when the charge and discharge current density is 3 mA / cm 2 After 80 cycles, the specific capacity can still be maintained at a stable level, with a charge area specific capacity of 0.85 mAh / cm 2 The capacity attenuation rate is about 60%. At the same time, the Coulomb efficiency remains above 98% after 15 cycles, and the Coulomb efficiency remains stable.

[0055] Example 3

[0056] In this embodiment, a method for preparing a negative electrode of a copper oxide lithium-ion battery with a hierarchical pore structure is provided, and the specific steps are as follows.

[0057] (1) Add 1 mL 1.5 mol / L CuCl 2 The solution was mixed evenly with 20 mL of N,N-dimethylformamide to obtain solution A. 0.5 mL of 4 mol / L NaOH solution was added to 0.5 mL of 3 mol / L SeO 2 The solution was mixed evenly to obtain solution B. Then, solution A and solution B were poured into a 50 mL reactor, and the reactor was placed in a forced air drying oven, set at 200 °C, and kept warm for 48 h.

[0058] (2) The CuSe prepared in step (1) 2 The nanoparticle precursor powder was filtered with a suction filter and washed with deionized water and anhydrous ethanol for 5 times. After washing, it was placed in a vacuum drying oven for drying at 50 °C for 24 h. The dried powder was pressed into tablets with a tablet press at a pressure of 80 MPa. 2The sheet was placed in a tube furnace, the heat treatment temperature was set to 900 °C, and the temperature was raised to 900 °C at a heating rate of 10 °C / min in an air atmosphere and kept at this temperature for 2 h for high temperature sintering. 2 Reacts with oxygen in the air to generate CuO and SeO 2 , SeO 2 The sublimation temperature of SeO is lower than 400 °C. Under the condition of heat treatment at 900 °C, 2 Vaporization will form nanoscale holes in the original position of the sheet; while CuSe 2 During the sintering process of the nanoparticles, due to the different sintering degrees between the particles, large pores of submicron to micron scale are formed between the particles, thus obtaining an integrated negative electrode of a copper oxide lithium-ion battery with a hierarchical pore structure.

[0059] SEM and XRD analysis showed that the phase composition of the negative electrode of the lithium ion battery prepared in this embodiment is CuO and Cu 2 The mixture of O has a microscopic morphology characterized by a composite of a submicron to micron-scale macroporous structure and a nanoscale microporous structure. The submicron to micron pores are evenly distributed throughout the negative electrode, and the nanopores are evenly distributed in the solid area separated by the submicron to micron pores. The macropore size distribution is roughly 0.7~10 μm, and the small pore size distribution is roughly 20~60 nm.

[0060] Example 4

[0061] In this embodiment, a method for preparing a negative electrode of a tin oxide lithium-ion battery with a hierarchical pore structure is provided, and the specific steps are as follows.

[0062] (1) Add 4 mL of 1 mol / L SnCl 4 The solution was mixed evenly with 20 mL of N,N-dimethylformamide to form solution A. 2 mL of 4 mol / L NaOH solution was added to 2 mL of 2 mol / L SeO 2 The solution was mixed evenly to obtain solution B. Then, solution A and solution B were poured into a 50 mL reactor, and the reactor was placed in a forced air drying oven, the temperature was set to 180 °C, and the temperature was kept for 72 h.

[0063] (2) The SnSe nanoparticle precursor powder obtained in step (1) is filtered with a suction filter, and the obtained nanoparticle precursor powder is washed with deionized water and anhydrous ethanol alternately for 4 times. After washing, it is placed in a vacuum drying oven for drying, the drying temperature is set to 100 °C, and the temperature is kept for 6 hours. The dried powder is pressed into tablets with a tablet press, and the pressure is set to 30 MPa. The SnSe sheet obtained in step (2) is placed in a tubular furnace, the heat treatment temperature is set to 800 °C, and the temperature is increased to 800 °C at a heating rate of 12 °C / min in an air atmosphere and kept for 2 hours for high-temperature sintering. During the sintering process, SnSe reacts with oxygen in the air to generate SnO 2 with SeO 2 , SeO 2 The sublimation temperature of SeO is lower than 400 °C. Under the condition of heat treatment at 800 °C, 2 During the sintering process, SnSe nanoparticles form micrometer-sized pores between the particles due to different sintering degrees between the particles, thus obtaining a hierarchical pore structure tin oxide lithium-ion battery integrated negative electrode.

[0064] SEM and XRD analysis showed that the phase composition of the negative electrode of the lithium ion battery prepared in this embodiment is SnO and SnO 2 The morphological characteristics of the mixture under the microscopic level are a combination of a micron-scale macroporous structure and a nano-scale small pore structure. The micropores are evenly distributed throughout the negative electrode, and the nanopores are evenly distributed in the solid area separated by the micropores. The pore size distribution of the macropores is approximately 15~25 μm, and the pore size distribution of the small pores is approximately 60~90 nm.

[0065] Example 5

[0066] In this embodiment, a method for preparing a negative electrode of a nickel oxide lithium-ion battery with a hierarchical pore structure is provided, and the specific steps are as follows.

[0067] (1) Add 1 mL 1 mol / L NiCl 2 The solution was mixed evenly with 20 mL of N,N-dimethylformamide to obtain solution A. 1 mL of 4 mol / L NaOH solution was added to 1 mL of 3 mol / L SeO 2 The solution was mixed evenly to obtain solution B. Then, solution A and solution B were poured into a 50 mL reactor, and the reactor was placed in a forced air drying oven, the temperature was set at 220 °C, and the reaction was continued for 24 h.

[0068] (2) The NiSe nanoparticle precursor powder obtained in step (1) is filtered with a suction filter, and the obtained nanoparticle precursor powder is washed with deionized water and anhydrous ethanol alternately for 5 times. After washing, it is placed in a vacuum drying oven for drying, the drying temperature is set to 60 °C, and the temperature is kept for 12 h. The dried powder is pressed into tablets with a tablet press, and the pressure is set to 40 MPa. The NiSe sheet obtained in step (2) is placed in a tubular furnace, the heat treatment temperature is set to 900 °C, and the temperature is increased to 900 °C at a heating rate of 13 °C / min in an air atmosphere and kept for 2 h for high-temperature sintering. During the sintering process, NiSe reacts with oxygen in the air to generate NiO and SeO 2 , SeO 2 The sublimation temperature of SeO is lower than 400 °C. Under the condition of heat treatment at 900 °C, 2 During the sintering process of NiSe nanoparticles, due to the different sintering degrees between particles, large pores of submicron to micron scale are formed between the particles, thus obtaining a graded pore structure nickel oxide lithium ion battery integrated negative electrode.

[0069] SEM and XRD analysis showed that the phase composition of the negative electrode of the lithium ion battery prepared in this embodiment is NiO and Ni 2 O 3 The morphological characteristics of the mixture under the microscopic level are a composite of submicron to micron-scale macropore structure and nanoscale micropore structure. The submicron to micron pores are evenly distributed throughout the negative electrode, and the nanopores are evenly distributed in the solid area separated by the submicron to micron pores. The pore size distribution of the macropores is roughly 0.8~6 μm, and the pore size distribution of the small pores is roughly 40~70 nm.

Claims

1. A method for preparing a negative electrode of a metal oxide lithium ion battery with a hierarchical pore structure, characterized in that: Here are the steps: (1) First, a mixed solution A of N,N-dimethylformamide and metal chloride and a mixed solution B of sodium hydroxide and selenium oxide are prepared respectively, and appropriate amounts of solution A and solution B are placed in a reaction kettle respectively, and mixed evenly using an ultrasonic machine, and then the reaction kettle is placed in a blast drying oven, the temperature is set to 100-300° C., and the temperature is kept for 12-72 hours. In the specific high temperature and high pressure environment in the reaction kettle, the metal chloride and selenium oxide react fully to obtain a metal selenide nanoparticle precursor powder; (2) filtering the metal selenide nanoparticle precursor powder obtained in step (1) with a suction filter, and washing the obtained nanoparticles. After washing, the powder is placed in a vacuum drying oven for drying. The dried powder is pressed into a whole sheet using a tablet press. The obtained metal selenide sheet is placed in a tubular furnace and set at a temperature between 500 and 1300° C. for high-temperature sintering. During the sintering process, the metal selenide reacts with oxygen in the air to generate metal oxides and selenium oxide. The sublimation temperature of selenium oxide is lower than 400° C. Therefore, at the above set temperature, the selenium oxide is vaporized, and nanometer-sized pores are formed at the original position in the sheet. During the sintering process, the metal selenide nanoparticles form submicron to micrometer-sized macropores between the particles due to different sintering degrees between the particles, thereby obtaining a hierarchical pore structure metal oxide lithium ion battery negative electrode. The application range of the hierarchical pore structure metal oxide lithium ion battery negative electrode includes iron oxide, copper oxide, tin oxide, and nickel oxide.

2. The method for preparing a negative electrode of a metal oxide lithium-ion battery with a hierarchical pore structure according to claim 1, characterized in that: Iron oxides include ferroferric oxide, ferric oxide, ferrous oxide, a mixture of ferroferric oxide and ferric oxide, a mixture of ferric oxide and ferrous oxide, a mixture of ferroferric oxide and ferrous oxide, and a mixture of ferroferric oxide, ferric oxide and ferrous oxide. Copper oxides include cupric oxide, cuprous oxide, and a mixture of cupric oxide and cuprous oxide. Tin oxides include tin dioxide, stannous oxide, and a mixture of tin dioxide and stannous oxide. Nickel oxides include nickel oxide, nickel nitride, and a mixture of nickel oxide and nickel nitride.

3. The method for preparing a negative electrode of a metal oxide lithium ion battery with a hierarchical pore structure according to claim 1, characterized in that: The thickness of the negative electrode of the hierarchical pore structure metal oxide lithium ion battery is 200 to 600 μm.

4. The method for preparing a negative electrode of a hierarchical pore structure metal oxide lithium ion battery according to claim 1, characterized in that: The macropore size in the negative electrode of the hierarchical pore structure metal oxide lithium ion battery is 0.4 to 25 μm, and the micropore size is 20 to 90 nm.

5. The method for preparing a negative electrode of a metal oxide lithium-ion battery with a hierarchical pore structure according to claim 1, characterized in that: In step (1), the concentration of metal chloride in solution A is 0.5-3 mol / L, and the volume ratio of N,N-dimethylformamide to metal chloride is 15:1-25:1; the concentration of selenium oxide in solution B is 0.5-3 mol / L, and the concentration of sodium hydroxide is 0.5-4 mol / L; and the volume ratio of solution A to solution B is 5:1-12:

1.

6. The method for preparing a negative electrode of a metal oxide lithium-ion battery with a hierarchical pore structure according to claim 1, characterized in that: In step (1), the insulation temperature of the reactor is 100 to 220° C., and the insulation time is 24 to 72 hours.

7. The method for preparing a negative electrode of a metal oxide lithium-ion battery with a hierarchical pore structure according to claim 1, characterized in that: In step (2), the drying temperature of the vacuum drying oven is 50 to 100° C., and the insulation time is 6 to 24 hours.

8. The method for preparing a negative electrode of a metal oxide lithium-ion battery with a hierarchical pore structure according to claim 1, characterized in that: In step (2), the metal selenide nanoparticle precursor powder is cleaned by alternately washing with deionized water and anhydrous ethanol for 4 to 5 times.

9. The method for preparing a negative electrode of a metal oxide lithium-ion battery with a hierarchical pore structure according to claim 1, characterized in that: In step (2), the pressure of using a tablet press to press the powder into tablets is 30 to 80 MPa.

10. The method for preparing a negative electrode of a metal oxide lithium-ion battery with a hierarchical pore structure according to claim 1, characterized in that: In step (2), the metal selenide sheet is placed in a tubular furnace for sintering at a heating rate of 10-15°C / min, a heat treatment temperature of 700-900°C, and a heat treatment time of 2-4h, thereby obtaining a metal oxide lithium ion battery negative electrode with a hierarchical pore structure.

Citation Information

Patent Citations

  • Hierarchical porous ferroferric oxide / graphene nano wire and preparation method and application thereof

    CN104157858A

  • Electrode with self-support structure, and preparation method thereof, and application thereof

    CN106876153A